Haematological malignancies following temozolomide treatment for paediatric high-grade glioma - Karremann, Michael; Kohl, Nadja; Kulozik, Andreas; Dürken, Matthias (European journal of cancer, 2017)
Background: Temozolomide (TMZ) is widely used in high-grade glioma (HGG). There is a major concern of treatment-induced secondary haematological malignancies (SHMs). Due to the poor overall survival of HGG patients, the true incidence is yet elusive. Thus, the aim of this study was to determine the risk of SHMs following TMZ in paediatric HGG. Methods: We analysed 487 patients from the HIT-HGG database of the German-speaking Society of Pediatric Oncology and Hematology with follow up beyond 1 year. Results: The incidence of SHM was 7.7 ± 3.2% at 10 years. No SHM occurred in 194 patients after first-line TMZ therapy, but four out of 131 patients treated with TMZ for relapse following first-line multiagent chemotherapy experienced SHM (20% at 10 years; p = 0.041). SHMs occurred in two out of 162 patients who underwent multiagent chemotherapy without TMZ (4.1% at 10 years). Gender, patient age and acute haematological toxicity during treatment did not affect the incidence of SHMs. Conclusion: Data of our cohort do not indicate an increased risk of SHM following TMZ treatment when compared to previous chemotherapy regimen. However, if TMZ is administered as a second-line treatment following conventional chemotherapy regimen, the risk might be disproportionately increasing.